Placental pseudo-malignancy from a DNA methylation perspective: unanswered questions and future directions - Novakovic, Boris; Saffery, Richard (Frontiers in Genetics, 2013)
The growing fetus is dependent on adequate placental function for delivery of essential nutrients and oxygen, and for waste removal. The placenta also plays an important protective role; shielding the developing baby from the maternal immune system and adverse environmental exposures. Fundamental to these processes is correct invasion of the decidua and remodelling of maternal vasculature, each of which show remarkable parallels to tumourogenesis, with the obvious exception that the former is usually a tightly controlled process. It is not surprising that these physiological similarities are mirrored in gene expression and epigenetic parallels, many not found in any other aspect of human development. In this perspective, we summarise known DNA methylation similarities between placenta and human tumours, and discuss the implications and knowledge gaps associated with these findings. We also speculate on the potential origin of common DNA methylation features in these two disparate aspects of human physiology.